ANALISIS PENGARUH JENIS PRICING STRATEGY TERHADAP KINERJA KEUANGAN UMKM DI MERCHANT TOKOPEDIA DAN SHOPEE - Immanuel Jonathan; Vincent Vincent; Juniarti Juniarti (Business Accounting Review, 2021)
In today’s internet era, customers can find out, access, and compare their information about products and prices easily from various competitors, so customers can find and decide which products to buy according to their wishes at the lowest prices. The problem that often occurs in every MSME in Indonesia is that many of MSMEs don’t perform calculations on production costs and aren’t precise in determining the selling price. As a result, the more products sold, the more products sold at a loss. Therefore, MSMEs must pay more attention to the selection of the type of pricing strategy to be applied. This study is intended to determine the effect of choosing the type of pricing strategy on the financial performance of MSMEs.The data-processing method is done by using inner model test, while the data-analysis method used is by using partial least squares and hypothesis testing derived from data collected from questionnaires that have been filled out and processed